2009
DOI: 10.1111/j.1530-0277.2009.00913.x
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Markers in the 3′ Region of the GluR5 Kainate Receptor Subunit Gene to Alcohol Dependence

Abstract: Background-Glutamate neurotransmission plays an important role in a variety of alcoholrelated phenomena, including alcohol self-administration by both animals and humans. Because the risk for alcohol dependence (AD) is genetically influenced, genes encoding glutamate receptors are candidates to contribute to the risk for AD. We examined the role of variation in the 3' region of GRIK1, the gene that encodes the GluR5 receptor subunit of the kainic acid glutamate receptor, on risk for AD. We focused specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 39 publications
1
53
1
Order By: Relevance
“…The direction is consistent with the reported significant differences in serum bicarbonate levels among patients grouped by rs4984241 genotype (18.500 2.345 mmol/l for AA, 21.184 2.598 mmol/ l for AG, and 22.043 2.602 mmol/l for GG, P = 0.015) [57] in that the A allele is associated with a lower bicarbonate level. A GRIK1 variant rs2832407 has been shown to be associated with alcohol dependence, adverse effects of topiramate, and serum levels of topiramate [58,59]. In our study, rs2832407 was not directly assessed, although other variants, such as rs462637 (in very weak LD with rs2832407, r 2 = 0.004, D ′ = 0.084), were nominally associated with topiramate-induced weight loss (P unadj = 0.001 for rs462637).…”
Section: Discussioncontrasting
confidence: 46%
“…The direction is consistent with the reported significant differences in serum bicarbonate levels among patients grouped by rs4984241 genotype (18.500 2.345 mmol/l for AA, 21.184 2.598 mmol/ l for AG, and 22.043 2.602 mmol/l for GG, P = 0.015) [57] in that the A allele is associated with a lower bicarbonate level. A GRIK1 variant rs2832407 has been shown to be associated with alcohol dependence, adverse effects of topiramate, and serum levels of topiramate [58,59]. In our study, rs2832407 was not directly assessed, although other variants, such as rs462637 (in very weak LD with rs2832407, r 2 = 0.004, D ′ = 0.084), were nominally associated with topiramate-induced weight loss (P unadj = 0.001 for rs462637).…”
Section: Discussioncontrasting
confidence: 46%
“…The GluR5 kainate receptor subunit, encoded by the GRIK1 gene, is a binding site for known mediators of glutamate neurotransmission, such as the anticonvulsant topiramate. An SNP located in the 3′ region of the GRIK1 gene, rs2832407C > A, has been associated with the risk for alcohol dependence [12]. However, the function of GRIK1 rs2832407C > A SNP remains unknown and further investigation is needed to ascertain whether it has a direct effect on GluR5 kainate receptor function or it is in linkage disequilibrium with functional variation elsewhere in the gene.…”
Section: Introductionmentioning
confidence: 98%
“…Glutamatergic neurotransmission genes have received particular attention, because alcohol-induced modulations in this system are associated with treatment efficacy, craving and relapse (Rietschel & Treutlein 2013). Recent studies found an association between alcohol addiction and single nucleotide polymorphisms (SNPs) in the sequence of genes that code for the N-Methyl-D-aspartate receptor (NMDAR) subunits, namely GRIN1 (rs2301363), GRIN2A (rs1650420) and GRIN2C (rs689730), as well as the kainate receptor (KAR) subunit GRIK1 (rs2832407) (Kranzler et al 2009;Reimers et al 2012;Kranzler 2014). The encoded proteins (NMDAR and KAR) are targets of the therapeutic agents acamprosate and topiramate, and studies have indicated that the GRIK1 polymorphism moderates topiramate's effects on the reduction of heavy drinking days (Kranzler et al 2014a, b).…”
Section: Introductionmentioning
confidence: 99%